Chemical composition of rainwater at EMEP station in Ankara, Turkey - Topçu, Sema; Incecik, Selahattin; Atimtay, Aysel T. (Elsevier BV, 2002)
Abstract The chemical characteristics of rainfall and its seasonal variation at the EMEP (The Cooperative Programme for Monitoring and Evaluation of the Long-Range Transmission of Air Pollutants in Europe) station located in Cubuk, Ankara were studied for the period between September 1994 and December 1996. The station is located in a rural area about 50 km north of Ankara and is considered as a background station for air pollution. The rainwater samples collected were analyzed for pH, major ions concentrations and conductivity. Seasonal variations for some major ions are pronounced. Generally, maximum concentrations appeared in winter or autumn, and minimum concentrations in spring or summer seasons. The average pH of rainwater samples is around 6.3 due to neutralization. Only about 4% of the rain samples had a pH below 5.0 and about 15% of the total rainwater samples had a pH below 5.6. This reflects strong inputs of alkaline species to rainwater samples in this location. The average pH of the samples higher than 5.6 observed in rural area of Ankara is due to a high loading of calcium ions in the form of CaCO 3 because of the alkaline nature of the soil. There is a strong relationship between pHs and other ions in summer. However, in winter, a weak relationship is found between SO 4 2− , NO 3 − , Na + and Mg 2+ . On the other hand, relationships between the conductivity and SO 4 2− concentration are stronger in summer than in winter. The low concentrations of H + found in rainwater samples from Cubuk suggests that an important portion of H 2 SO 4 and HNO 3 have been neutralized by alkaline particles in the atmosphere. Weak correlations are found between the hydrogen ions and SO 4 2− or NO 3 − ions for all seasons because of neutralization of these ions with alkaline particles. The dust-rich local and surrounding limestone environment might have caused the high concentration of Ca 2+ in Cubuk area. The relatively high concentration of NH 4 + observed at Cubuk is suspected to be due to surrounding agricultural activity. This agricultural activity has been found to be effective not only in spring, but also in autumn and winter to cause neutralization of the rainwater.